Berättelsen Vamlingbo prästgård: Kulturarvsproduktion och fantiserade händelser - Oscarsson, Tony (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2006)
This article is based on fieldwork and interviews carried out around a newly opened cultural heritage site on the southern part of Gotland. My purpose is to suggest an alternative way of understanding cultural heritage. In the article I discuss activities appearing in the potential spaces that emerge when places are recontextualized in connection with cultural heritage production. My investigation unveils some of the methods in which concepts about local past, present and future are being promoted. The fact that cultural heritage sites are becoming more frequent around the globe can be understood both as a reaction to local socio-economic problems and as an ideological response to arguments about the necessity of remembering local pasts.